Analysis of Critical Thought Wahbah Wahbah az-Zuḥailī Concerning Determination Separations - qosim, qosim (LP2M IAIN Palangka Raya, 2016)
ABSTRACT This title of this study is An Analysis of Critical Thought Wahbah Wahbah az-Zuḥailī Concerning Determination Separations. The purpose of this study was to assess the Wahbah az-Zuḥailī thinking about the establishment of divorce, legal istinbath methods used , as well as the relevance of thought Wahbah az-Zuḥailī the context of divorces in Indonesia.The type of this study is library research (library research) . Data collected by using dokumentatif . While the method used in this study are fiqh, uṣul fiqhapproach and contextual historical approach.The results of the study showed that the determination of divorce divided into two divorces that do not require a court judgment and divorce which require a court decision. Separations that do not require a court decision is divorce by pronouncing talaq and khuluk . While divorce is a divorce requires a court decision that caused his wife to go to court and divorce taasuf .The underlying thought Wahbah az-Zuḥailī are the legal consequences of divorce and the seat of the court as an institution that handles divorce cases. Law istinbath method used is based on the HR at-Tirmidhi about divorce joke, Bukhari about the events of Ibn Umar that mentalak his wife in a state of menstruation, QS. al-Baqarah verse 231 and HR Ibn Majah on the prohibition of doing immorility. Relevance thought Wahbah az-Zuḥailī the context of divorces in Indonesia can be seen in taasuf divorce procedures and the validity of divorce outside the court on condition that the assembly had dug legal facts that can be used as strong evidence for a divorce. Key word; Determination Separations, Wahbah az-Zuḥailī.